FEW POST-LARVAL STAGES AND JUVENILES OF THE SARDINE, SiRDISELLA DAYI REGAN - Bensam, P (Indian Journal of Fisheries, 2011)
Sardinella dayi contributes to a minor extent to the sardine fishery of the Tuticorin area in the Gulf of Mannar. A few post-larval stages of this species in the size range of 1870mnj.—20.25 mm and juveniles of 28 mm—36 mm are described. The food of the post-larvae consisted mainly of copepods. A discussion on the identity of the larvae and juveniles as those of S. dayi is given based on circumstancial evidence and characteristic features distinguishing them from similar stages of related species.